Digital Temperature Tracking in Porous Media Burners - Salinas-Silva, R; Raff-Biggemann, U; Henriquez-Vargas, L (SAGE Publications Ltd, 2012)
Combustion in porous media burners presents considerable advantages over free flame burners due to several outstanding features inter alia clean and highly efficient combustion properties allowing a considerable amount of feedback energy from the flame area to preheat the mixture of fuel and air resulting in a considerable reduction of unavoidable pollutant formations appearing e.g. as the emission of CO and NOx. In addition, porous media burners are manufactured in highly compact small sizes suitable to industrial and household heating characteristic applications. Heat transfer between solid and gas depends mainly on the porous thermophysical properties of the component known as the solid matrix. These systems are characterized by the formation of a combustion flame pulse or wave which can travel inside the burner, depending on the operating conditions at velocities of about 0.1 mm/s. In this paper, a new temperature tracking scheme is proposed based on digital image processing to determine the position and the velocity of the thermal profile. Results showed reduced errors in the estimation of the peak temperature position using digital image analysis compared to conventional thermocouple-based measurements techniques.